The impact of diabetes and social, biologic and behavioral determinants of health on liver cancer risk - Shouman, Marwa; Jaffa, Ayad A.; Jaffa, Miran A. (Frontiers in Endocrinology, 2025)
BackgroundLiver cancer has seen a concerning rise in incidence, currently ranked as the sixth most prevalent cancer. Diabetes, along with indices of social, biological, and behavioral determinants of health, was linked to the risk of liver cancer.AimWe aim to determine the effect of diabetes and selected indices of determinants of health on liver cancer.MethodsOur quantitative study is based on a sample of 239,006 US participants adopted from the BRFSS-2022 data. Our results are summarized using frequency distributions and weighted percentages. Weighted logistic regressions were employed to determine the associations with liver cancer.ResultsIn this sample population, 73 individuals experienced liver cancer, 12.17% (n=33,776) had diabetes, with a four-fold increase in the odds of liver cancer for individuals with diabetes (OR: 4.27, CI: 1.73-10.57). Employment status, educational level, urban/rural living, smoking status were determinants of health associated with liver cancer as well. Our subgroup analysis focusing exclusively on those diagnosed with liver cancer following their diabetes diagnosis confirmed diabetes as risk factor for liver cancer (OR: 5.44, 95%CI: 1.58-18.70), along with marital status and other determinants of health.ConclusionEffective diabetes management and addressing key health determinants are crucial for reducing liver cancer risk and improving prevention and treatment outcomes.